Influences of Online Behavioral Ad Avoidance among Sri Lankans: Mediating Role of Negative Experience - Manathunga, M.M.S.S; Wijenayake, S.I (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2021)
Influences of Online Behavioral Ad Avoidance Among Sri Lankans: Mediating Role of Negative Experience.Abstract: Online advertising has emerged over the years and it is slowly dominating the traditional marketing communication strategies irrespective of the industry or the product. Investments on online behavioral advertisements (OBA) have increased and at the same time there are implications in practice of avoiding online behavioral advertisement manually and using ad avoiding software. Online behavioral advertising is identified as a major challenge for digital marketing. Therefore, this study attempts to identify the influencing factors of online ad avoidance. Through literature, Goal Impediment (GI), Privacy Concern (PC), Ad Irritation (AI), Negative Experience (NE) and Retargeting (RI) were identified as the key influences and their impact on online behavioral advertising is explored. Further, there are implications in literature that Negative Experience shows a mediating impact. To examine the impact of the key influences identified with online behavioral advertising, quantitative approach is used. 10 hypotheses are developed, and a structured questionnaire is used to collect data from a convenient sample of 300 from the Western province. To test the hypotheses, Partial Least Square (PLS) structural equation modeling with SPSS and SmartPLS tools. All the direct hypotheses and the mediating hypotheses were supported by the data. The study results show that, negative experience was affected by goal impediment, privacy concern and ad irritation. Results of the study shows that negative experience play a significant mediating role between the key influences and the online behavioral ad avoidance. Retargeting has significant impact on online behavioral advertising. Study findings offer some valuable insights to online behavioral advertisers in their strategy formulations, policy making and ethical concerns. These implications can benefit the digital advertising industry to improve the return on the investment in terms of viewership and exposure.
Keywords: Ad Irritation, Goal Impediment, Negative Experience, Online Behavioral Advertising, Privacy Concern, Retargeting